Karangwangi people's (South Cianjur, West Java, Indonesia) local knowledge of species, forest utilization and wildlife conservation - RUHYAT PARTASASMITA; JOHAN ISKANDAR; NICHOLAS MALONE (Biodiversitas Journal of Biological Diversity, 2016)
Partasasmita R, Iskandar J. Malone N. 2015. Karangwangi people's (South Cianjur, West Java, Indonesia) local knowledge of species, forest utilization and wildlife conservation. Biodiversitas 17: 154-161. In the past, many West Javan Villages had a high diversity of wildlife. Nowadays, however, the diversity of wildlife in these villages has tended to decrease rapidly. This is caused by many factors, including the loss or destruction of wildlife habitat destruction, intensive use of pesticides in the agricultural sector, and illegal hunting. Animal hunting is typically undertaken by villagers for various purposes, such as to fulfill household meet consumption, as well as for the capture and trading of pets. Traditionally, the use of wildlife by the Sundanese people of West Java is influenced by corpus (local knowledge) and cosmos (beliefs). As a result, the wild animals have been utilized within a sustainable system that enables wildlife conservation. Today, however, a lot of traditional knowledge or local knowledge of wildlife has eroded. This paper elucidates local knowledge of Karangwangi villagers of Subdstrict of Cidaun, District of Cianjur, Province of West Java, Indonesia on variousÂ species, utilization, and the conservation of wildlife. Methods used in this study are a combination of qualitative and quantitative techniques based on an ethnozoological approach. The result of study shows that the respondents recognize at least 45 species of wildlife consisting of 15 mammalian species, 21 species of Aves, and 9 species of herpetofauna. Based on the perception of respondents, those wildlife species have various socio-economic and cultural saliences (eg. household meat consumption, pets, trading, and appearing in mythology), as well as various ecological functions (e.g., crop pests, pest controls, and seed dispersal). Some cultural myths related with wildlife have been recorded and partly determine the utilization of wildlife by village people.